Application of net zero extended exergy buildings concept for sustainable buildings analysis. (1st June 2023) - Açikkalp, Emin; Hepbasli, Arif; Palmero-Marrero, Ana I.; Borge-Diez, David
Abstract: Different Zero-Energy Building (ZEB)-related definitions considering its four main dimensions, such as zero energy, zero carbon, zero exergy and zero cost, have been proposed by different investigators. Among these, exergy-based definitions are relatively low in numbers. In this regard, the main objective of this present study is to propose net zero extended exergy buildings as a new concept, which combines extended exergy and net zero exergy building concepts and is a measure of the exergetic footprint. This concept setups a balance between extended exergy accounting of electricity from the grid and electricity generated in building. The proposed methodology is applied to a building available in the literature for heating and cooling seasons. Results show that 450Wp peak power and 44.181 kWh electrical energy must be obtained for meeting the electricity demand of the building. Another novel result is that the extended exergy accounting of the electricity generated by PV panels is bigger than the extended exergy of the electricity taken from the gird meaning that exergetic footprint of the electricity generated by PV panels is bigger. However, this result must be interpreted for the whole life time of the system. Graphical abstract: Image 1 Highlights: A novel method for sustainable buildings analysis is presented. Method combines extended exergy and net zero exergy building concepts. Exergetic footprint of the building is obtained. A case study is presented and used to validate the methodology. Results prove that exergy analysis shows the global exergy amount for the building.